Pemanfaatan Strategi Pembelajaran Kontekstual dalam Pembelajaran PAI - Muhammad Zaid; Abdurrahman Almubasyir; Gusmaneli Gusmaneli (IHSANIKA : Jurnal Pendidikan Agama Islam, 2025)
This research discusses the utilization of contextual learning strategies in learning Islamic Religious Education (PAI). The method used in this research is literature study by analyzing various relevant literatures. The results of the study show that contextual learning can encourage students to find the relationship between the material learned and the real world situation, encourage students to apply their learning outcomes in real life, and involve students in discovering material through the process of direct experience. However, in its implementation there are challenges faced, such as the CTL strategy takes a long time for students to understand all the material, teachers must work extra to be more intensive in guiding, student errors in trying to connect subjects with the reality of everyday life. Therefore, proper handling is needed in optimizing the use of contextual learning in PAI learning.